2013
DOI: 10.4172/2157-7609.1000145
|View full text |Cite
|
Sign up to set email alerts
|

Pyridostigmine Bromide and Potassium Iodate: Subacute Oral Toxicity and Stability

Abstract: Subacute toxicity of pyridostigmine bromide (PB) and potassium iodate (PI) tablets upon forty five days administration were assessed by changes in body weight, hematology, serum biochemical parameters and histopathology of rat liver and kidney. LD 50 of PB was estimated to be 66.9 mg/kg. At dose of 45 mg/kg/day showed decrease in body weight and liver weight with cytoplasmic acidophilic bodies and vesicular steatosis signifying hepatocellular injury. Kidney tissue developed neutrophil polymorph infiltration wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…We hypothesize that the feeding conditions may have contributed to the weight gain observed in both the control group and the group administered a dose of 7.2 mg/kg/day; whereas rabbits in the higher dosage group may have experienced adverse effects on their feeding capacity, resulting in insignificant weight gain. These results are consistent with the findings reported by Bigoniya et al [4].…”
Section: Results Of Subchronic Toxicity Assessmentsupporting
confidence: 94%
See 2 more Smart Citations
“…We hypothesize that the feeding conditions may have contributed to the weight gain observed in both the control group and the group administered a dose of 7.2 mg/kg/day; whereas rabbits in the higher dosage group may have experienced adverse effects on their feeding capacity, resulting in insignificant weight gain. These results are consistent with the findings reported by Bigoniya et al [4].…”
Section: Results Of Subchronic Toxicity Assessmentsupporting
confidence: 94%
“…These results are consistent with prior investigations by Morgan and Kluwe [6], [7]. Similarly, a study conducted by Bigoniya observed non-significant elevations in AST and ALT levels in rats orally administered PB at a dose of 45 mg/kg for 45 days, with no discernible effect on blood protein levels [4].…”
Section: Results Of Subchronic Toxicity Assessmentsupporting
confidence: 93%
See 1 more Smart Citation